2019
DOI: 10.3390/ma12081226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Jute Fiber Modification on Mechanical Properties of Jute Fiber Composite

Abstract: Recently, the demand for reinforced plastics from natural, sustainable, biodegradable, and environmentally friendly fibers has been rising worldwide. However, the main shortcoming of natural fibers reinforced plastics is the poor compatibility between reinforcing fibers and the matrix. Hence, it is necessary to form a strong attachment of the fibers to the matrix to obtain the optimum performance. In this work, chemical treatments (acid pretreatment, alkali pretreatment, and scouring) were employed on jute fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(74 citation statements)
references
References 20 publications
2
72
0
Order By: Relevance
“…The characteristic peak of jute at 2900 cm −1 indicates C-H stretching in methyl and methylene groups in the cellulose and hemicellulose. The C-O stretching in the glycosidic linkage of the cellulose is observed at 1042 cm −1 band [56]. Moreover, some of the cellulose absorbance bands at 662, 895, 1423, and 2883 cm −1 can be detected in figure 10 [50].…”
Section: Ftir Analysismentioning
confidence: 99%
“…The characteristic peak of jute at 2900 cm −1 indicates C-H stretching in methyl and methylene groups in the cellulose and hemicellulose. The C-O stretching in the glycosidic linkage of the cellulose is observed at 1042 cm −1 band [56]. Moreover, some of the cellulose absorbance bands at 662, 895, 1423, and 2883 cm −1 can be detected in figure 10 [50].…”
Section: Ftir Analysismentioning
confidence: 99%
“…In recent years, fiber-reinforced polymer (FRP) composites have been widely used in the field of civil and architectural engineering as retrofitting or reinforcing material. This is due to their high strength and stiffness, low weight, and corrosion resistance [1][2][3][4][5]. Certainly, the development of FRP composite materials is accompanied by many challenges that must be seriously considered to achieve more extensive application of FRP materials in the construction fields.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were carried out to investigate the possibility of PLA-reinforced natural fiber to improve biocomposite properties. It has been reported that different types of fiber such as hemp, flax, jute, bamboo, and kenaf as well as sisal were used, because of the abundant availability, low price, low density, and excellent mechanical properties [12][13][14][15]. Most of these studies revealed that some properties like tensile and flexural strength were improved.…”
Section: Introductionmentioning
confidence: 99%